ANALYSIS OF FACTORS AFFECTING GOVERNMENT AGENCY PERFORMANCE : A STUDY ON SURABAYA CITY GOVERNMENT - Alifia Kusuma Putri; Dyah Ratnawati (LPPM STIE Muhammadiah Bandung, 2025)
The purpose of this study is to examine how Surabaya City government agencies' performance is impacted by workload, internal control systems, and budget target clarity. These three factors are taken into account since they strategically contribute to the efficacy and efficiency of public services. Employees from 20 Regional Agency were given questionnaires as part of a quantitative data collection process, and multiple linear regression was used for analysis. The analysis's findings demonstrate that workload, internal control, and budget target clarity all significantly impact government agencies' performance at the same time. Workload has the most significant impact of the three. This result demonstrates that balanced task management is just as important as planning and supervision when it comes to efforts to enhance bureaucratic performance. In order to improve the effectiveness of public services at the local level, the study's recommendations suggest that internal control systems be strengthened, more targeted budgets be created, and tasks be distributed more fairly.